Perception of COVID-19 impacts on the construction industry over time. Issue 1 (31st December 2022) - Rokooei, Saeed; Alvanchi, Amin; Rahimi, Mostafa
Abstract: The emergence of COVID-19 has been changing in the world since 2020 and prompted social, cultural, and economic systems to adjust their structures, routines, and processes. The economic aspects of the pandemic appeared soon, and many industries changed their workflow and procedures through a mandatory or recommended quarantine. Knowing the impact of COVID-19 on different areas of construction projects, concerns and considerations, and preparedness levels of corresponding entities helps construction managers to cope with the new situation. The main purpose of this study was to investigate the impact of COVID-19 on construction professionals' perceptions over time. For this purpose, a longitudinal study was conducted to explore the perception of construction professionals toward COVID-19 impact and how it is changed over time. In this study, construction professionals from two countries with relatively similar timing for the pandemic outbreak participated in three rounds of surveys conducted six months apart. A total of 567 responses were collected, and statistical tests were conducted to examine the frequency and intensity level of COVID-19 impact as well as similarities and differences between different rounds. The novelty of this study is the exploration of the pandemic impacts over time and the exhibition of perception's evolution. The statistical analyses showed a significant change in the perception of professionals in both regions. The results indicated a high level of COVID-19 impact on various construction aspects. The results also emphasized that the preparedness of related entities should be improved to manage raised concerns at different scales of construction professions.